Energy Efficiency and Sustainability through Wind Power for Green Hospitals - Balo, Figen; Yilmaz, Unal; Sua, Lutfu S. (Bloomsbury Publishing Plc., 2021)
[Abstract Not Available]
Keywords: Sustainable development; Wind power; Energy; Power; Energy efficiency